INTERACTIVE INTERNET-BASED DISASTER RISK INFORMATION SYSTEM FOR TSUNAMI-HIT ACEH PROVINCE OF INDONESIA (Journal of Information and Communication Technology, 2016)
Aceh is facing not only tsunami threats, such as the 2004 Indian Ocean Tsunami that caused massive devastation to the region, but also other natural disasters, such as earthquakes, landslides and volcanic eruptions. One of the factors that can contribute to reducing disaster is the availability and accessibility of risk knowledge. This knowledge is essential to keep people aware and well prepared to face impending disasters. This study proposes an interactive internet-based disaster risk management information system (DRMIS) for the Aceh province. The DRMIS serves as an online disaster risk map as well as a tool for communicating risk knowledge. An iterative approach to designing, developing and implementing the system is introduced. The DRMIS, which is currently accessible online, and its features, are described. The proposed system offers interactive display of four thematic maps, covering hazards, vulnerability, capacity and disaster risk of the most common natural hazards in Aceh.